Remodeling of triacylglycerol synthesis in emerging oilseed crops: genetic engineering for high-value seed oil - Alkotami, Linah M. (Kansas State University, 2024)
The utilization of vegetable oils, which predominantly consist of triacylglycerols (TAG), for diverse industrial purposes is hindered by many challenges due to their unfavorable physical properties. To overcome this constraint, metabolic engineering studies have focused on modifying plant seeds to produce oil with improved physical properties in non-food crops. However, altering oil composition to generate novel TAG molecules has proven to be challenging due to pathway bottlenecks and their potential impact on plant growth and seed viability. One unique class of TAG, known as acetyl-1,2-diacyl-sn-glycerols (acetyl-TAG), naturally constitutes more than 90% of the seed oil in Euonymus species. Acetyl-TAG is characterized by a distinct structure in which an sn-3 acetate replaces the long acyl group found in regular TAG. Consequently, acetyl-TAG oil exhibits lower viscosity, making it advantageous for applications as an emulsifiers, lubricants, or "drop-in" biofuel. Previous attempts to produce acetyl-TAG in oilseed crops such as soybean (Glycine max), Camelina sativa, and pennycress (Thlaspi arvense) have only achieved an average of 45-80% acetyl-TAG. The primary objective of this study is to engineer acetyl-TAG production in oilseed crops to match the highest naturally occurring levels in Euonymus seeds. Furthermore, the study aims to investigate the impact of acetyl-TAG on plant growth, seed properties, seed lipids, and global gene expression. The non-food crops camelina and pennycress were chosen due to their ease of transformation using an Agrobacterium-mediated floral-dip method. To achieve the desired outcome, multiple strategies were employed. Initially, an acetyltransferase enzyme (EfDAcT) from Euonymus fortunei seeds, known for its higher activity compared to the previously used Euonymus alatus enzyme (EaDAcT), was introduced. Subsequently, the endogenous TAG-synthesizing enzyme DGAT1, which competes with EfDAcT for the diacylglycerol (DAG) substrate, was inhibited. Lastly, EfDAcT was expressed in FATTY ACID ELONGASE1 (FAE1) mutant lines to enhance acetyl-CoA availability for acetyl-TAG synthesis while eliminating very long-chain fatty acids (VLCFA), which are unfavorable substrates for EfDAcT. Using these strategies, transgenic plants capable of producing 98% acetyl-TAG in pennycress seeds and 93% acetyl-TAG in camelina seeds were generated. Compared to wild-type seeds, transgenic seeds exhibited higher accumulation of TAG and polar lipids, while maintaining comparable or slightly lower levels of total fatty acid content. Seeds that produced high levels of acetyl-TAG showed a slight delay in germination with no significant impact on plant growth. Global transcript levels in camelina transgenic seeds indicated changes in gene expression, including those involved in flavonoid biosynthesis and hormone response. Overall, this study demonstrates the feasibility of achieving nearly complete alteration of the type of oil synthesized by a plant and offer valuable insights into the genetic and metabolic mechanisms underlying lipid biosynthesis.
Keywords: Acetyl-TAG; Euonymus fortunei; Camelina sativa; Pennycress; Plant lipids